Vibration-damping rubber composition and vibration-damping rubber member

The vibration-proof rubber composition, with a specific blend of diene rubber, surface-active carbon black, and HAF class carbon black, addresses the challenge of achieving low dynamic magnification and durability, ensuring effective vibration reduction and long-term performance in vehicles.

JP2025054960AActive Publication Date: 2025-04-08SUMITOMO RIKO CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023164218
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

Vibration-proof rubber compositions for vehicles face a challenge in achieving both low dynamic magnification and durability, as carbon black with high iodine adsorption improves durability but worsens dynamic magnification.

Method used

A vibration-proof rubber composition containing diene rubber, surface-active carbon black with high hydrogen generation, and HAF class carbon black, with a specific ratio of surface-active carbon black to the total amount of both carbon blacks, to achieve low dynamic magnification and durability.

Benefits of technology

The composition effectively achieves low dynamic magnification and excellent durability, making it suitable for use in electric vehicles by maintaining spring properties and improving long-term performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054960000002
    Figure 2025054960000002
  • Figure 2025054960000003
    Figure 2025054960000003
  • Figure 2025054960000001
    Figure 2025054960000001
Patent Text Reader

Abstract

To provide a vibration-damping rubber composition and a vibration-damping rubber member which are capable of combining low dynamic magnification and high durability.SOLUTION: Provided is a vibration-damping rubber composition comprising the components (A) to (C) below, wherein the total amount of (B) and (C) is 20 to 70 pts.mass relative to 100 pts.mass of (A), and the proportion of (B) in the total amount of (B) and (C) is 50 to 90 pts.mass. Also provided is a vibration-damping rubber member prepared using the composition. (A) is a diene rubber. (B) is a surface-active carbon black having a value (Hc), which is defined as the amount of hydrogen generated per gram of carbon black when heated to 1980°C, of 4500 ppm or more. (C) is HAF-grade carbon black.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an anti-vibration rubber composition and an anti-vibration rubber member, and more particularly to an anti-vibration rubber composition and an anti-vibration rubber member suitable for anti-vibration rubber for vehicles such as automobiles. [Background technology]

[0002] Anti-vibration rubber compositions are used in automobiles to reduce vibration and noise. Since the vulcanizates (anti-vibration rubber members) of such anti-vibration rubber compositions need to have high rigidity and strength and suppress vibration transmission, it is required to reduce the value of the dynamic magnification ratio [dynamic spring constant (Kd100) / static spring constant (Ks)] (reducing the dynamic magnification ratio). Conventionally, measures to reduce the dynamic magnification ratio have been taken, for example, by using carbon black as a reinforcing agent in anti-vibration rubber compositions and controlling factors such as the amount of carbon black blended, particle size, structure, etc. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 7037986 Summary of the Invention [Problem to be solved by the invention]

[0004] Meanwhile, automobile vibration-proofing materials are also required to have durability, i.e., performance that does not deteriorate the vibration-proofing performance and supporting rigidity even with long-term use. Carbon black with a large iodine adsorption amount has the effect of improving durability, but the tradeoff is that it deteriorates the dynamic magnification ratio.

[0005] An object of the present invention is to provide an anti-vibration rubber composition and an anti-vibration rubber member that can achieve both low dynamic magnification and durability. [Means for solving the problem]

[0006] In order to solve the above problems, the anti-vibration rubber composition of the present invention contains the following components (A) to (C), the total amount of (B) and (C) is 20 parts by mass or more and 70 parts by mass or less per 100 parts by mass of (A), and the proportion of (B) to the total amount of (B) and (C) is 50% by mass or more and 90% by mass or less. (A) Diene rubber (B) Surface-activated carbon black, which has a hydrogen emission amount (Hc) of 4500 ppm or more per gram of carbon black when heated to 1980°C. (C) HAF grade carbon black

[0007] The total amount of (B) and (C) is preferably 30 parts by mass or more and 50 parts by mass or less with respect to 100 parts by mass of (A). The ratio of (B) to the total amount of (B) and (C) is preferably 60% by mass or more and 80% by mass or less. The iodine adsorption amount of (C) is preferably 50 g / kg or more.

[0008] The anti-vibration rubber member according to the present invention is formed from a vulcanizate of the anti-vibration rubber composition according to the present invention.

[0009] The anti-vibration rubber member according to the present invention can be suitably used for electric vehicles.

[0010] (1) The anti-vibration rubber composition according to the present invention contains the following components (A) to (C), the total amount of the (B) and the (C) is 20 parts by mass or more and 70 parts by mass or less per 100 parts by mass of the (A), and the ratio of the (B) to the total amount of the (B) and the (C) is 50% by mass or more and 90% by mass or less. (A) Diene rubber (B) Surface-activated carbon black, which has a hydrogen emission amount (Hc) of 4500 ppm or more per gram of carbon black when heated to 1980°C. (C) HAF grade carbon black

[0011] (2) In the above (1), the total amount of (B) and (C) may be 30 parts by mass or more and 50 parts by mass or less per 100 parts by mass of (A).

[0012] (3) In the above (1) or (2), the ratio of (B) to the total amount of (B) and (C) may be 60% by mass or more and 80% by mass or less.

[0013] (4) In any one of the above (1) to (3), the iodine adsorption amount of the (C) is preferably 50 g / kg or more.

[0014] (5) The anti-vibration rubber member according to the present invention is formed from a vulcanizate of the anti-vibration rubber composition according to any one of (1) to (4) above.

[0015] (6) In the above (5), the vibration-isolating rubber member according to the present invention may be for an electric vehicle. Effect of the Invention

[0016] According to the anti-vibration rubber composition of the present invention, since it contains the above components (A) to (C) and the above components (B) and (C) are present in specific proportions, it is possible to achieve both low dynamic magnification and durability.

[0017] When the total amount of (B) and (C) is 30 parts by mass or more and 50 parts by mass or less per 100 parts by mass of (A), the durability is improved and the dynamic magnification is easily reduced.

[0018] When the ratio of (B) to the total amount of (B) and (C) is 60% by mass or more and 80% by mass or less, the durability is improved and the dynamic magnification is easily reduced.

[0019] When the iodine adsorption amount of the (C) is 50 g / kg or more, the durability is improved.

[0020] Furthermore, since the anti-vibration rubber member according to the present invention is constituted by a vulcanizate of the anti-vibration rubber composition according to the present invention, it is possible to achieve both low dynamic magnification and durability.

[0021] The anti-vibration rubber member according to the present invention can be suitably used for electric vehicles. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a distribution diagram of dynamic magnification (spring characteristics) versus hardness, comprising data from examples and comparative examples. [Diagram 2] FIG. 2 is a distribution diagram of durability versus hardness, comprising data from examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The anti-vibration rubber composition and the anti-vibration rubber member according to the present invention will be described in detail below.

[0024] The anti-vibration rubber composition according to the present invention (hereinafter sometimes simply referred to as anti-vibration rubber composition) contains the following components (A) to (C), with (B) and (C) being present in specific proportions. (A) Diene rubber (B) Surface-activated carbon black, which has a hydrogen emission amount (Hc) of 4500 ppm or more per gram of carbon black when heated to 1980°C. (C) HAF grade carbon black

[0025] The diene rubber (A) is the main component of the rubber component of the anti-vibration rubber composition. The main component of the rubber component refers to a component that accounts for 50% by mass or more of the entire rubber component of the anti-vibration rubber composition. The anti-vibration rubber composition is greatly affected by the properties of the diene rubber (A), which is the main component of the rubber component. Examples of the diene rubber (A) include natural rubber (NR), butadiene rubber (BR), styrene-butadiene rubber (SBR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile-butadiene rubber (NBR). These are used alone or in combination as the diene rubber (A). Among these, natural rubber is preferably used from the viewpoint of achieving both strength, durability, and low dynamic magnification.

[0026] The surface active carbon black (B) has a high reinforcing effect and maintains the spring characteristics without deteriorating the dynamic magnification of the vibration-proof rubber composition. As described above, the surface active carbon black (B) has a value (Hc) of 4500 ppm or more, calculated as the amount of hydrogen generated per gram of carbon black when heated to 1980°C. If the Hc is 5000 ppm or more, it is preferable because it has better surface activity. The amount of hydrogen is derived from hydrogen atoms of organic groups, such as hydroxyl groups and carboxy groups, that are covalently bonded to carbon atoms of the carbon black.

[0027] The measurement of the amount of hydrogen is carried out, for example, as follows. That is, first, in order to remove the adsorbed components of the carbon black, 20 mg of carbon black, which has been degassed and dried in a vacuum dryer at 125°C for 4 hours, is placed in a tin capsule, and a high-sensitivity hydrogen analyzer (EMGA-621 manufactured by Horiba, Ltd., using a TCD detector) is used to thermally decompose the carbon black in a graphite crucible at 1980°C for 70 seconds. Then, the generated gas is passed through a high-temperature oxidizing agent, a room-temperature oxidizing agent, a carbon dioxide removing agent, and a desiccant by a carrier gas (inert argon gas) at a constant flow rate (400 ml / min), and separated in a column. Then, the hydrogen gas obtained is quantified by a detector (thermal conductivity method).

[0028] The surface active carbon black (B) may be used alone or in combination of two or more kinds, so long as it has the above-mentioned hydrogen amount.

[0029] From the viewpoints of durability and low dynamic magnification, the surface active carbon black (B) preferably has an iodine adsorption of 14 g / kg or more and 28 g / kg or less. The iodine adsorption of the carbon black is a value measured in accordance with JIS K 6217-1 (method A). Moreover, from the viewpoints of durability and low dynamic magnification, the surface active carbon black (B) preferably has a DBP absorption of 118 ml / 100 g or more and 132 ml / 100 g or less. The DBP absorption of the carbon black is a value measured in accordance with JIS K 6217-4.

[0030] HAF grade carbon black (C) is a carbon black with high wear resistance for furnaces, and is classified as N300 series carbon black according to ASTM D1765. From the viewpoint of durability and low dynamic magnification, HAF grade carbon black (C) preferably has an iodine adsorption of 50 g / kg or more. More preferably, it is 50 g / kg or more and 100 g / kg or less, and even more preferably, it is 60 g / kg or more and 90 g / kg or less. Moreover, from the viewpoint of durability and low dynamic magnification, HAF grade carbon black (C) preferably has a DBP absorption of 50 ml / 100 g or more and 110 ml / 100 g or less.

[0031] HAF grade carbon black (C) is a carbon black with a large amount of iodine adsorption. The use of HAF grade carbon black (C) improves durability. On the other hand, the dynamic magnification ratio deteriorates. For this reason, when HAF grade carbon black (C) is used alone, it is not possible to achieve both a low dynamic magnification ratio and durability. Surface active carbon black (B) has a high reinforcing effect and has the effect of maintaining the spring characteristics without deteriorating the dynamic magnification ratio of the vibration-proof rubber composition. And, by using surface active carbon black (B) together with HAF grade carbon black (C), it is possible to achieve both a low dynamic magnification ratio and durability.

[0032] The total amount of (B) and (C) is 20 parts by mass or more and 70 parts by mass or less relative to 100 parts by mass of (A). If the total amount of (B) and (C) is too small, the reinforcing effect is small, the rigidity (static spring constant) is low, and durability is low. If the total amount of (B) and (C) is too large, the rigidity is high but the durability is low. In addition, the dynamic magnification ratio is deteriorated. By keeping the total amount of (B) and (C) within the above range, it is possible to achieve both a low dynamic magnification ratio and durability. From the viewpoints of excellent durability improvement effect and ease of achieving a low dynamic magnification ratio, the total amount of (B) and (C) is more preferably 25 parts by mass or more and 60 parts by mass or less, and even more preferably 30 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of (A).

[0033] The ratio of (B) to the total amount of (B) and (C) is 50% by mass or more and 90% by mass or less. If the ratio of (B) is too low, the spring characteristics are poor and the dynamic magnification ratio deteriorates. If the ratio of (B) is too high, durability cannot be satisfied. By keeping the ratio of (B) within the above range, a low dynamic magnification ratio and durability can be achieved at the same time. From the viewpoints of excellent durability improvement effect and ease of achieving a low dynamic magnification ratio, the ratio of (B) to the total amount of (B) and (C) is more preferably 55% by mass or more and 85% by mass or less, and even more preferably 60% by mass or more and 80% by mass or less.

[0034] The content of (B) is preferably 10 parts by mass or more, more preferably 12.5 parts by mass or more, and even more preferably 15 parts by mass or more, per 100 parts by mass of (A), from the viewpoint of facilitating a low dynamic magnification, etc. The content of (B) is preferably 63 parts by mass or less, more preferably 54 parts by mass or less, and even more preferably 45 parts by mass or less, per 100 parts by mass of (A), from the viewpoint of ensuring the content of (C) and achieving an excellent effect of improving durability, etc.

[0035] The content of (C) is preferably 2 parts by mass or more, more preferably 2.5 parts by mass or more, and even more preferably 3 parts by mass or more, per 100 parts by mass of (A), from the viewpoint of excellent durability improving effect, etc. The content of (B) is preferably 35 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 25 parts by mass or less, per 100 parts by mass of (A), from the viewpoint of ensuring the content of (B) and easily achieving a low dynamic magnification, etc.

[0036] The anti-vibration rubber composition according to the present invention may contain, in addition to the above-mentioned components (A) to (C), appropriate additives, etc. Examples of the additives include vulcanizing agents, vulcanization accelerators, vulcanization aids, antioxidants, process oils, etc.

[0037] Examples of the vulcanizing agent include sulfur (powdered sulfur, precipitated sulfur, insoluble sulfur) and sulfur-containing compounds such as alkylphenol disulfide. These may be used alone or in combination of two or more. Sulfur is more preferable.

[0038] The content of the vulcanizing agent is preferably in the range of 0.1 to 10 parts by mass, particularly preferably in the range of 0.3 to 5 parts by mass, based on 100 parts by mass of the diene rubber (A). If the content of the vulcanizing agent is too low, crosslinking reactivity tends to deteriorate. If the content of the vulcanizing agent is too high, rubber physical properties (breaking strength, breaking elongation) tend to deteriorate.

[0039] When sulfur is used as a vulcanizing agent, the content of sulfur is preferably within a range of 1 to 2.5 parts by mass relative to 100 parts by mass of the diene rubber (A). More preferably, it is within a range of 1.5 to 2 parts by mass. By making the content of sulfur 1 part by mass or more, the crosslink density can be ensured and the decrease in the static spring constant can be suppressed. In addition, by making the content of sulfur 2.5 parts by mass or less, excellent heat resistance can be obtained.

[0040] Examples of the vulcanization accelerator include thiuram-based, sulfenamide-based, guanidine-based, thiazole-based, aldehyde ammonia-based, aldehyde amine-based, and thiourea-based vulcanization accelerators. These are used alone or in combination of two or more. Among these, a combination of a thiuram-based vulcanization accelerator and at least one vulcanization accelerator selected from the sulfenamide-based, guanidine-based, and thiazole-based vulcanization accelerators is preferred because it provides excellent compression set.

[0041] The content of the vulcanization accelerator is preferably in the range of 0.1 to 10 parts by mass, particularly preferably in the range of 0.3 to 5 parts by mass, based on 100 parts by mass of the diene rubber (A).

[0042] Examples of thiuram vulcanization accelerators include tetramethylthiuram disulfide (TMTD), tetraethylthiuram disulfide (TETD), tetrabutylthiuram disulfide (TBTD), tetrakis(2-ethylhexyl)thiuram disulfide (TOT), tetrabenzylthiuram disulfide (TBzTD), and the like.

[0043] Examples of sulfenamide vulcanization accelerators include N-oxydiethylene-2-benzothiazolylsulfenamide (NOBS), N-cyclohexyl-2-benzothiazolylsulfenamide (CBS), Nt-butyl-2-benzothiazolesulfenamide (BBS), N,N'-dicyclohexyl-2-benzothiazolesulfenamide, etc. These may be used alone or in combination of two or more kinds.

[0044] Examples of the guanidine vulcanization accelerator include N,N'-diphenylthiourea, trimethylthiourea, N,N'-diethylthiourea, N,N'-dibutylthiourea, etc. These may be used alone or in combination of two or more kinds.

[0045] Examples of thiazole-based vulcanization accelerators include dibenzothiazyl disulfide (MBTS), 2-mercaptobenzothiazole (MBT), 2-mercaptobenzothiazole sodium salt (NaMBT), and 2-mercaptobenzothiazole zinc salt (ZnMBT). These are used alone or in combination of two or more. Among these, dibenzothiazyl disulfide (MBTS) and 2-mercaptobenzothiazole (MBT) are preferably used because of their excellent crosslinking reactivity.

[0046] Examples of the vulcanization aid include zinc oxide (ZnO), stearic acid, magnesium oxide, etc. These may be used alone or in combination of two or more.

[0047] The content of the vulcanization aid is preferably in the range of 0.1 to 10 parts by mass, particularly preferably in the range of 0.3 to 7 parts by mass, based on 100 parts by mass of the diene rubber (A).

[0048] Examples of the antiaging agent include amine-based antiaging agents, imidazole-based antiaging agents, carbamate-based antiaging agents, phenol-based antiaging agents, and quinoline-based antiaging agents. These may be used alone as the antiaging agent, or two or more may be combined. As the antiaging agent, it is preferable to use an amine-based antiaging agent and an imidazole-based antiaging agent in combination.

[0049] The content of the antioxidant is preferably in the range of 0.5 to 15 parts by mass, and particularly preferably in the range of 1 to 10 parts by mass, based on 100 parts by mass of the diene rubber (A).

[0050] Examples of amine-based antiaging agents include those having a diphenylamine skeleton, those having a phenylenediamine skeleton, those having a dihydroquinoline skeleton, etc. Specific examples include 2,2,4-trimethyl-1,2-dihydroquinoline oligomers, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, 4,4'-bis(4-α,α-dimethylbenzyl)diphenylamine, and N,N'-di-β-naphthyl-p-phenylenediamine.

[0051] The mixing ratio of the amine-based antiaging agent is preferably in the range of 1 to 10 parts by mass, and particularly preferably in the range of 2 to 5 parts by mass, per 100 parts by mass of the diene rubber (A).

[0052] Examples of process oils include naphthenic oils, paraffinic oils, aromatic oils, etc. These may be used alone or in combination of two or more.

[0053] The content of the process oil is preferably in the range of 1 to 35 parts by mass, particularly preferably in the range of 3 to 30 parts by mass, based on 100 parts by mass of the diene rubber (A).

[0054] The anti-vibration rubber composition according to the present invention can be prepared by kneading the components (A) to (C) and other materials added as necessary using a kneading machine such as a kneader, a Banbury mixer, an open roll, or a twin-screw mixer.

[0055] The anti-vibration rubber composition according to the present invention becomes an anti-vibration rubber member (vulcanizate) by vulcanizing at high temperature (150 to 170°C) for 5 to 30 minutes. The anti-vibration rubber member made of the vulcanizate of the anti-vibration rubber composition according to the present invention can be advantageously used in automotive anti-vibration rubber applications such as motor mounts, suspension bushes, subframe mounts, etc. for engine automobiles and electric automobiles powered by electric motors (including fuel cell automobiles (FCVs), plug-in hybrid vehicles (PHVs), hybrid vehicles (HVs), etc. in addition to electric automobiles (EVs)).

[0056] According to the vibration-proof rubber composition of the present invention having the above-mentioned configuration, the diene rubber (A) is blended with the surface-active carbon black (B) and the HAF-grade carbon black (C). Since the above (B) and (C) are in a specific ratio, it is possible to achieve both a low dynamic magnification and durability.

[0057] In the anti-vibration rubber composition according to the present invention, from the viewpoint of being suitable for electric vehicles, etc., the static spring constant Ks is preferably 300 N / mm or more and 1000 N / mm or less. More preferably, it is 400 N / mm or more and 750 N / mm or less. By adopting the above configuration, the anti-vibration rubber composition according to the present invention can make the static spring constant Ks within the above range.

[0058] As described above, the embodiments of the present invention have been described. However, the present invention is not limited to the above embodiments at all, and various modifications are possible without departing from the spirit of the present invention.

Examples

[0059] Hereinafter, the present invention will be described in detail using examples and comparative examples.

[0060] The materials used are as follows. <Component A> · Natural rubber (NR) <Component B> · Surface-active carbon black (CB): "SPHERON5200" manufactured by Cabot Japan (Hc: 5200 ppm, iodine adsorption amount 24 g / kg, DBP absorption amount 124 ml / 100 g) <Component C> · HAF grade carbon black (CB)<1>: "VULCAN 3D" manufactured by Cabot Japan, iodine adsorption amount 81 g / kg, DBP absorption amount 101 ml / 100 g) · HAF grade carbon black (CB)<2>: "SEAST 300" manufactured by Tokai Carbon, iodine adsorption amount 86 g / kg, DBP absorption amount 75 ml / 100 g) <Others> · Surface-inactive carbon black (CB): "SEAST SO" (FEF grade) manufactured by Tokai Carbon, iodine adsorption amount 44 g / kg, DBP absorption amount 115 ml / 100 g) · Zinc oxide: "Zinc Oxide Type 2" manufactured by Sakai Chemical Industry · Stearic acid: "Lunac S30" manufactured by Kao · Process oil: "Suncen 4130" manufactured by Nippon Sun Oil Amine-based antioxidants <1> : Seiko Chemical's "Ozonone 6C" Amine-based antioxidants <2> : "Nonflex RD" manufactured by Seiko Chemical ·Vulcanization accelerator <1> : "Noccela CZ" manufactured by Ouchi Shinko Chemical ·Vulcanization accelerator <2> : "Noccela TBT" manufactured by Ouchi Shinko Chemical Sulfur (vulcanizing agent)

[0061] (Examples 1 to 5, Comparative Examples 1 to 5) The materials were mixed in the ratios shown in the table, and then mixed using an internal mixer (Banbury type) or rolls to prepare rubber compositions. The properties of the prepared rubber compositions were measured and evaluated according to the following methods.

[0062] 〔hardness〕 Each rubber composition was press molded and vulcanized at 150°C for 20 minutes to prepare a rubber sheet having a thickness of 2 mm. A JIS No. 5 dumbbell was punched out from the rubber sheet, and the hardness (JIS A) was measured using the dumbbell in accordance with JIS K 6251. In the table, the hardness of Example 1 was set to 100, and each value was expressed as an index.

[0063] [Static spring constant (Ks)] Using each rubber composition, a rubber test piece was prepared by pressing and vulcanizing a disk-shaped metal fitting (diameter 60 mm, thickness 6 mm) onto the top and bottom surfaces of a rubber piece (diameter 50 mm, height 25 mm) under vulcanization conditions of 170°C x 30 minutes. Next, the rubber test piece was compressed 7 mm in the cylindrical axial direction, and the loads at deflections of 1.5 mm and 3.5 mm were read from the load deflection curve of the second forward movement to calculate the static spring constant (Ks (N / mm)). In the table, the static spring constant (Ks) of Example 1 was set to 100, and each value was shown as an index.

[0064] [Dynamic spring constant (Kd100)] The rubber test piece was compressed 2.5 mm in the cylindrical axial direction, and a constant displacement harmonic compression vibration of 0.05 mm amplitude and 100 Hz frequency was applied from below centered on the position of this 2.5 mm compression, and the dynamic load was detected by a load cell above to calculate and measure the dynamic spring constant (Kd100 (N / mm)) in accordance with JIS K 6394. In the table, the dynamic spring constant (Kd100) of Example 1 was set to 100, and each value was expressed as an index.

[0065] [Dynamic magnification (Kd100 / Ks)] The dynamic magnification was calculated as the dynamic spring constant (Kd100) / static spring constant (Ks). In the table, the dynamic magnification (Kd100 / Ks) of Example 1 is set to 100, and each value is shown as an index.

[0066] [Durability] Each rubber composition was press molded (vulcanized) under conditions of 150°C x 30 minutes to prepare a rubber sheet with a thickness of 2 mm. Then, a JIS No. 3 dumbbell was punched out from this rubber sheet, and a stretch fatigue test was performed using this dumbbell in accordance with JIS K 6260 to measure the number of times of durability. In the table, each value is shown as an index, with the number of times of durability of Example 1 being 100.

[0067] [Spring characteristic evaluation for hardness] The data for each example and comparative example were plotted with hardness (index) on the horizontal axis and dynamic magnification (index) on the vertical axis to create a distribution diagram in Figure 1. As shown in Figure 1, it can be seen that the spring characteristics versus hardness tend to rise to the right overall. Using an approximation line as the standard, in Figure 1, anything below this line (the dotted line rising to the right in Figure 1) is marked with an "O" and anything above it is marked with an "X".

[0068] [Durability evaluation against hardness] The data for each example and comparative example were plotted with hardness (index) on the horizontal axis and durability count (index) on the vertical axis to create a distribution diagram in Figure 2. As shown in Figure 2, it can be seen that durability count versus hardness generally tends to decline to the right. Using an approximation line as the basis, in Figure 2, values ​​above this line (the dotted line sloping downward to the right in Figure 2) are marked with an "O" and values ​​below this line are marked with an "X".

[0069] 〔comprehensive evaluation〕 If both the spring characteristics relative to hardness and the durability relative to hardness were "good", then the sample was rated "good", and if either one was "bad", then the sample was rated "bad".

[0070] [Table 1]

[0071] In Comparative Example 1, surface active carbon black (B) is not used for diene rubber (A), and HAF grade carbon black (C) is used alone. In Comparative Example 1, the dynamic magnification ratio to hardness is poor, and the spring characteristics are poor. In Comparative Example 2, surface active carbon black (B) is not used for diene rubber (A), and FEF grade carbon black is used instead. That is, FEF grade carbon black with a small iodine adsorption amount and HAF grade carbon black (C) with a large iodine adsorption amount are used in combination. In Comparative Example 2, the durability is poor. In Comparative Example 3, HAF grade carbon black (C) is not used for diene rubber (A), and surface active carbon black (B) is used alone. In Comparative Example 3, the durability is poor. In Comparative Example 4, surface active carbon black (B) and HAF grade carbon black (C) are used in combination for diene rubber (A), but the total amount used is too large. In Comparative Example 4, the dynamic magnification ratio to hardness is poor, and the spring characteristics are poor. In addition, the durability is also poor. In Comparative Example 5, the diene rubber (A) is used in combination with surface-active carbon black (B) and HAF-grade carbon black (C), but the amount of surface-active carbon black (B) used is too small. In Comparative Example 5, the dynamic magnification ratio relative to hardness is poor, and the spring characteristics are poor.

[0072] On the other hand, in the examples, surface active carbon black (B) and HAF grade carbon black (C) are blended with diene rubber (A), with (B) and (C) being in a specific ratio. In the examples, the dynamic magnification to hardness is good, and the spring characteristics are excellent. In addition, the durability is also excellent.

[0073] From the above, according to the examples and comparative examples, it can be seen that by blending surface-active carbon black (B) and HAF-grade carbon black (C) with diene rubber (A) and by using a specific ratio of (B) and (C), it is possible to achieve both low dynamic magnification and durability.

[0074] Although the embodiments and examples of the present invention have been described above, the present invention is not limited to the above-mentioned embodiments and examples, and various modifications are possible without departing from the spirit and scope of the present invention.

Claims

1. Contains the following components (A) to (C): The total amount of (B) and (C) is 20 parts by mass or more and 70 parts by mass or less with respect to 100 parts by mass of (A), A vibration-proof rubber composition, wherein a ratio of the (B) to a total amount of the (B) and the (C) is 50 mass % or more and 90 mass % or less. (A) Diene rubber (B) A surface active carbon black having an amount of hydrogen generated when heated to 1980° C. per gram of carbon black (Hc) of 4500 ppm or more. (C) HAF grade carbon black

2. 2. The anti-vibration rubber composition according to claim 1, wherein the total amount of said (B) and said (C) is 30 parts by mass or more and 50 parts by mass or less per 100 parts by mass of said (A).

3. 3. The anti-vibration rubber composition according to claim 1, wherein a ratio of said (B) to a total amount of said (B) and said (C) is 60% by mass or more and 80% by mass or less.

4. 3. The vibration-proof rubber composition according to claim 1, wherein the iodine adsorption amount of said (C) is 50 g / kg or more.

5. An anti-vibration rubber member comprising a vulcanizate of the anti-vibration rubber composition according to claim 1.

6. The anti-vibration rubber member according to claim 5 , which is for an electric vehicle.

Citation Information

Patent Citations

  • Rubber composition having excellent dynamic properties

    JP1991054235A

  • Preparation of rubber composition containing dinitrodiamine

    JP1991170539A

  • Rubber composition excellent in dynamic properties

    JP1991223353A

  • Vibration-proofing rubber composition

    JP1996269239A

  • Vibrationproof rubber composition and vibrationproof rubber made therefrom

    JP2004292586A